POTENTIAL HAZARDS OF WORK ACCIDENTS IN CONSTRUCTION PROJECTS TERMINAL CONSTRUCTION - Puspita, Asri Dwi; Chanif, Much Fajar; Santoso, Gempur; Lailyah, Ilvy Nur (Universitas Maarif Hasyim Latif, 2024)
Occupational Safety and Health” (K3) is an effort to overcome potential hazards or health and health risks that may occur. Occupational Safety Risks are still often overlooked. The construction service industry is one of the industrial sectors that has a risk of work accidents. The frequent occurrence of work accidents on construction projects causes a lack of attention to K3. In this research and final project, we will examine the application of OSH in project construction. Identify any OHS risks that may occur in building construction work and analyze those risks. Risk analysis to find out the most common OHS risks in building construction work based on the results of a questionnaire distributed to respondents who work in the building construction sector. K3 risk will be analyzed using HIRARC (Hazard Identification, Risk Assessment & Risk Control). Next, we will make risk control recommendations to provide solutions to the health and safety risks that have been analyzed. Based on the results of this study, there were 12 potential hazards for foundation work, 14 potential hazard for structure work, 13 hazard for roofing work, 9 potential hazard for finishing work, and 9 MEP work for hazard potential.